A family of high gain fuel cell front-end converters with low input current ripple for PEMFC power conditioning systems. (3rd August 2021) - Huangfu, Yigeng; Ma, Yuhui; Bai, Hao; Xu, Liangcai; Wang, Aiben; Ma, Rui
Abstract: Since the output voltage of the proton exchange membrane fuel cell (PEMFC) is relatively low and load-dependent, a high-performance fuel cell front-end converter is required to achieve boost and power regulation in PEMFC systems. In response, a novel family of high gain fuel cell front-end converters with low input current ripple is proposed. The proposed topologies can substantially improve the voltage gain through the expansion and combination of active switched-inductor networks and passive switched-capacitor units. The introduced interleaved parallel structure is convenient to limit the current ripple on the input side to prevent accelerated aging of fuel cells, which is another prominent advantage. Meanwhile, the converters can achieve the automatic current sharing between parallel inductors and the low voltage stress on active switches and diodes. In this paper, the fuel cell model and topology derivation of the high gain fuel cell front-end converters are first analyzed. Then, it further describes the operating mode and steady-state performance of converters under the inductor current continuous conduction mode. The comparison with other converters shows that this converter is suitable for connecting the PEMFC to the high voltage DC bus. Finally, a 200 W, 20/180 V converter prototype is implemented, and the simulation and experiment prove the theoretical correctness and validate the superior performances of the proposed converters. Graphical abstract: Image 1 Highlights: A novel family of fuel cell front-end converters is developed for PEMFC systems. Switched-capacitor and switched-inductor are combined to improve voltage gain. The interleaved structure enables the converters to reduce the input current ripple. The converters can achieve low voltage stress on all power semiconductors. Experiment and comparison verify the feasibility of fuel cell interfacing converters.